PENGARUH VOLATILITAS HARGA COCOA DUNIA TERHADAP EKSPOR COCOA INDONESIA - Agung Prasetyo; Mahananto (JURNAL ILMIAH AGRINECA, 2020)
Cocoa was one of the commodities, which are crucial to the economy of Indonesia. Cocoaserve as a source of income, driving the development of the region, a provider of employment and agro-industry and foreign exchange earnings, The purpose of this study to analyze the influence of the world cocoa price volatility against Indonesian cocoa exports. This study used ordinary least squares (OLS) to analyze the data. The time interval used was 2013-2017 with monthly data. The results showed that independent variables such as world cocoa prices, consumption and world stocks of cocoa have a significant effect on the Indonesian cocoa exports. World cocoa prices were down led to a decline of Indonesian cocoa exports. Besides that, Government policy states the imposition of export duty on exported goods to guarantee the supply of raw materials for cocoa in the country, OLS also indicates that cocoa production, exchange rate, and world cocoa consumption did not affect the export cocoa of Indonesia.